The degree of creative leadership practice among principals of governmental basic schools in the city of Hebron from the teachers’ point of view - Asafra, Hanadi Asaad Amer (Journal of Educational and Psychological Sciences, 2023)
This study aimed to identify the degree of practicing creative leadership among principals of governmental basic schools in Hebron from the teachers’ point of view. The descriptive analytical approach was used, and a questionnaire for data collection. The study was conducted on a sample consisting of (53) male and female teachers from public basic schools in Hebron. The results showed that the general total score on the practicing of creative leadership among the principals of governmental basic schools in Hebron came with a total average of (3.45) with a moderate degree The level of dimensions; After sensitivity to problems, he obtained the highest average (3.91), with a high degree, then flexibility with (3.76). Thirdly, fluency, with an average of (3.50), and finally originality, with an average of (3.28), all with a (medium) degree. The results showed that there were no statistically significant differences for the variables (gender, educational qualification, and years of experience). In light of the results of the study, the researcher recommended encouraging principals to develop creative leadership skills, enhancing teamwork within the school, teachers’ participation in solving problems, and enhancing principals’ abilities to reflect on issues and see things from different ways.